Cultivating Teacher Resilience 2020
DOI: 10.1007/978-981-15-5963-1_17
|View full text |Cite
|
Sign up to set email alerts
|

Navigating Changing Times: Exploring Teacher Educator Experiences of Resilience

Abstract: While there exists notable research in Australia and internationally on the ways pre-service and early career teachers develop and maintain resilience, there is a paucity of literature examining the resilience of teacher educators. The teacher education landscape has a dynamic nature, and in the Australian context, there have been multiple changes to policy and accreditation that have impacted on the work of teacher educators, including: the introduction of literacy and numeracy testing and a teaching performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Significantly, a recent scoping review of what is known about TE wellbeing, stress, and burnout (see Turner & Garvis, 2023) revealed that globally only thirteen studies were conducted in this field between 2016 and 2022, with most reporting on studies from the United States (see, for example, Coyle et al, 2020;Sharp et al, 2018;Padilla & Thompson, 2016). Only two studies were undertaken solely in the Australian context (Gillett-Swan & Grant-Smith, 2020;McDonough et al, 2021) with another international study of TE wellbeing in Canada, the United States, Australia, and England (Kosnik et al, 2017).…”
Section: Issues Affecting Teacher Educator Wellbeingmentioning
confidence: 99%
See 3 more Smart Citations
“…Significantly, a recent scoping review of what is known about TE wellbeing, stress, and burnout (see Turner & Garvis, 2023) revealed that globally only thirteen studies were conducted in this field between 2016 and 2022, with most reporting on studies from the United States (see, for example, Coyle et al, 2020;Sharp et al, 2018;Padilla & Thompson, 2016). Only two studies were undertaken solely in the Australian context (Gillett-Swan & Grant-Smith, 2020;McDonough et al, 2021) with another international study of TE wellbeing in Canada, the United States, Australia, and England (Kosnik et al, 2017).…”
Section: Issues Affecting Teacher Educator Wellbeingmentioning
confidence: 99%
“…Findings of these studies suggest that exhaustion, burnout and low levels of wellbeing are common for TEs due to factors such as workload intensification and excessive workload (McDonough et al, 2021;Kosnik et al, 2017), job insecurity (Kiltz et al, 2020), supporting student wellbeing (Gillet-Swan & Grant-Smith, 2020; Kiltz et al, 2020), perceived lack of institutional support (Gillet-Swan & Gran-Smith, 2020; Coyle et al, 2020) and teacher-researcher role conflict whereby teacher educators often assume significant teaching responsibilities which are not valued by their institutions (Padilla &Thompson, 2016) Apart from these few studies, limited address of wellbeing has been made regarding TEs and even more specifically those in Australia. Turner and Garvis (2023) concluded from their scoping review that TE wellbeing, stress, and burnout are relatively new and under-researched areas.…”
Section: Issues Affecting Teacher Educator Wellbeingmentioning
confidence: 99%
See 2 more Smart Citations
“…Tantangan ini sebenarnya juga memberikan peluang guru untuk meninggalkan profesinya. Riset juga menunjukkan bahwa tuntutan akuntabilitas, perubahan kebijakan pendidikan, dan kapasitas individu untuk bertahan, memiliki peran yang signifikan dalam membentuk resiliensi guru (Mcdonough et al, 2020). Disini lain, peran ganda tersebut dipandang oleh subjek penelitian untuk mencapai keunggulan diri.…”
Section: Berkerja Dengan Value (Bernilai) Bertahap Dalam Keadaan Sulitunclassified